A system dynamics approach to venture capital investments illustrated by cases from singapore (Asian Journal of Economics and Business Management, 2022)
Despite the amount of research on VC decision-making, very little is known about the dynamic decision processes venture capitalists (VCs) execute in the real world, paying attention to the systemic interactions within the industry. The importance of dynamic decision processes lies in recognizing that investment decisions in VC take place in complex, rapidly changing, and highly competitive markets where growth and returns are expected to be significantly higher. The objective of this paper is to create and simulate a quantitative model of VC investment dynamics drawing on cases from Singapore. The geographic focus is on Singapore and in terms of methodology, the paper makes use of System Dynamics. As key findings, our model captures how the boom-and-bust phenomenon may be generated by the economic agents’ intendedly rational decisions within a competitive VC market, that, however, leads to unintended poor performance for the industry as a whole. Future research could then compare our simulation results not only with each other or to the base run, but also to other kinds of scenarios; for example, an external shock like a market crash scenario.